Capacitors for improved power cycling
By introducing a stable mock agent layer between the conductive polymer layers of the electrolytic capacitor, the problem of poor stability of the capacitor during the power cycle is solved, and higher capacitor stability and performance are achieved.
Patent Information
- Application Number
- CN202210149192.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-18
- Filing Date
- 2022-02-18
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-02-18
AI Technical Summary
The existing electrolytic capacitors have poor stability during power cycles, and are prone to delamination or breakdown of the conductive polymer layer, resulting in capacitor failure.
A stable mock agent layer is introduced between the conductive polymer layers, including a specific mock agent compound (Formula A), to improve the stability of the conductive polymer layer and reduce breakdown during power cycles.
By introducing a mock agent layer, the stability of the capacitor in the power cycle is significantly improved, the capacitor's capacitance loss and equivalent series resistance (ESR) are reduced, and the overall performance of the capacitor is improved.
Smart Images

Figure CN114974900B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to improvements in electrolytic capacitors, and more particularly to improvements in capacitance stability during cycling. More particularly, the present invention relates to an improved electrolytic capacitor including a mordant layer that improves capacitance stability. Background Art
[0002] Electronic devices are increasingly expected to have higher functionality and to last longer without failure. The effort to provide these benefits has impacted every component of the electronic device. The present invention is directed to eliminating failure modes that occur at the electronic component level, particularly within electrolytic capacitors.
[0003] Solid electrolyte capacitors have become a staple in the development of electronic components. Solid electrolytic capacitors, especially those using valve metal anodes, initially appeared to contain a pressed powder anode with a dielectric on the anode and manganese dioxide as a conductive layer on the dielectric, with the manganese dioxide as the cathode. Manganese dioxide was replaced by capacitors containing conductive polymers as the cathode layer, in part because of the non-combustion failure mode of the capacitors. Of these solid electrolytic capacitors, capacitors containing polythiophene-based conductive polymers have proven to be the most ideal.
[0004] As demand continues to increase, those skilled in the art continue to improve valve metal capacitor manufacturing technology to produce powders with higher charge densities, such as 50,000 CV / g or more. As the charge density of the powder increases, the internal surface area of the anode formed from the powder increases and the pore size of the pressed powder decreases. This complicates the use of a conductive polymer cathode because it is difficult to deposit the conductive polymer on the interstitial surface of the anode to the extent that it covers a sufficient amount of the dielectric.
[0005] The problem of poor interstitial surface area coverage is significantly alleviated by applying multiple layers of conductive polymers, where the inner and outer layers are different formulations. One method that has been very successful is to form a primary conductive polymer layer directly on the dielectric by in-situ polymerization, where the monomers of the polymer are polymerized in situ. Although this is conducive to forming the initial layer, the outer layer of the conductive polymer is preferably formed from a slurry of a preformed conductive polymer. The conductive polymer slurry is prepared from a dispersion of PEDOT: polyanion particles and other additives in water. The polyanion can be polystyrene sulfonic acid or its copolymer. Such polyanion copolymers are described in U.S. Patent 10,340,091. An alternative method is to form a primary conductive polymer layer from a slurry of a preformed conductive polymer, wherein the slurry has very small conductive polymer particles, including conductive polymer particles below the detectable limit, where the conductive polymer is soluble in this article. Both methods are conducive to coating the interstitial region of the porous anode to form a coating on the dielectric thereon. Then, a secondary conductive layer is preferably formed on the primary conductive polymer layer by depositing a slurry containing a preformed conductive polymer.
[0006] Using different formulations or techniques to deposit the conductive polymers results in reduced capacitor stability, especially during power cycling. Without being bound by theory, it is speculated that the polymer layers are incompatible or the pores are insufficiently filled, or a charge barrier is formed. Incompatibility of adjacent layers may lead to delamination during power cycling within the polymer layer itself or in the dielectric. The creation of a charge barrier, known as anomalous charge current, may lead to failure of the conductive polymer layer, the mechanism of which is not yet understood.
[0007] Provided herein is a novel mordant layer positioned between adjacent conductive polymer layers, wherein the mordant layer mitigates delamination or breakdown of a conductive polymer cathode. Summary of the invention
[0008] The present invention relates to an improved capacitor comprising a mordant layer which is stable, particularly under power cycling.
[0009] A particular feature of the present invention is the mordant layer which improves the stability of the conductive polymer layer, wherein breakdown of the polymer layer, especially upon power cycling, is mitigated.
[0010] Another feature of the present invention is the ability to manufacture improved capacitors having the described mordant layer using existing manufacturing methods.
[0011] These and other advantages are provided as will be achieved in an electrolytic capacitor. The electrolytic capacitor includes an anode comprising a dielectric layer on the anode. A primary conductive polymer layer is located on the dielectric layer, and a mordant layer is located on the primary conductive polymer layer, wherein the mordant layer comprises a mordant compound of formula A:
[0012]
[0013] Among them, R 1 -R 6 Each independently selected from H and -PO(OR 7 )2, where each R 7 is independently selected from H, substituted or unsubstituted alkyl containing 1-20 carbon atoms, substituted or unsubstituted aryl containing 6-20 carbon atoms or alkylaryl containing 7-21 carbon atoms; provided that R 1 -R 6 At least one of them is -PO(OH)2. The secondary conductive polymer layer is located on the mordant layer.
[0014] Another embodiment provides a method of forming an electrolytic capacitor. The method includes:
[0015] forming an anode;
[0016] forming a dielectric on the anode;
[0017] forming a primary conductive polymer layer on the dielectric;
[0018] forming a mordant layer on the primary conductive layer, wherein the mordant layer comprises a mordant compound of formula A;
[0019]
[0020] Among them, R 1 -R 6 Each independently selected from H and -PO(OR 7 )2, where each R 7 is independently selected from H, substituted or unsubstituted alkyl containing 1-20 carbon atoms, substituted or unsubstituted aryl containing 6-20 carbon atoms or alkylaryl containing 7-21 carbon atoms; provided that R 1 -R 6 At least one of them is -PO(OH)2; and
[0021] A secondary conductive polymer layer is formed on the mordant layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A schematic cross-sectional view of one embodiment according to the present invention is shown.
[0023] Figure 2 A flow chart according to one embodiment of the present invention is shown. DETAILED DESCRIPTION
[0024] The present invention relates to an improved electrolytic capacitor that exhibits significantly improved stability over cycles of multiple power cycling tests. More specifically, the present invention relates to an electrolytic capacitor that includes a mordant between adjacent applied conductive polymer layers, wherein the mordant reduces failures associated with conductive polymer layer failure.
[0025] The invention will be described with reference to the accompanying drawings, which form an integral but non-limiting part of the description provided for the clarity of the invention.
[0026] Will refer to Figure 1 One embodiment of the present invention is described. Figure 1 In the figure, a capacitor 10 of the present invention is schematically shown in a cross-sectional view. The capacitor includes an anode 12, which is preferably a porous block formed by pressing a powder. An anode wire 14 extends from the anode. The anode wire can be embedded in the powder before pressing, which is preferred, or the anode wire can be attached to the anode surface after pressing, for example, by welding. A dielectric 16 is formed on the anode surface. Although shown as a layer of uniform thickness, the actual dielectric layer is located on the interstitial surface of the porous block. A primary conductive polymer layer 18 is located on the dielectric, preferably extending into the interstitial surface of the block to increase the surface area of the conductive polymer coating on the dielectric. Although shown as a single layer, for discussion purposes, the primary conductive polymer layer is generally used for a variety of applications. A mordant layer 20 is formed on the primary conductive polymer layer, wherein the mordant layer comprises a mordant compound of formula A described below and an optional but preferred crosslinking agent. A secondary conductive polymer layer 22 is formed on the mordant layer. An adhesive layer 24 is optionally but preferably formed on the secondary conductive polymer layer. The adhesive layer allows the cathode lead 26 to be electrically connected to the secondary conductive polymer layer, such as by welding or conductive adhesive means. It is known in the art that connecting the lead to the conductive polymer layer is difficult, and an adhesive layer is typically used to allow good physical and electrical contact between the secondary conductive polymer layer and the cathode lead. The anode lead 28 is in electrical contact with the anode wire. An optional but preferred electrically insulating resin 30 encapsulates all but the bottom of the cathode and anode leads.
[0027] Will refer to Figure 2 A method of forming an electrolytic capacitor is described. Figure 2In the present invention, a method for forming an electrolytic capacitor is presented as a flow chart. An anode is prepared at 40. The anode can be a foil or can be prepared by pressing a powder. The pressed powder anode preferably contains an anode wire extending therefrom. A sintered anode is preferred, especially when niobium or tantalum powder is used as the anode powder. At 42, a dielectric is formed on the anode. The method for forming the dielectric is not limited to typical methods known to those skilled in the art that are suitable for demonstrating the present invention. At 44, a primary conductive polymer layer is formed on the dielectric. The primary conductive polymer layer is formed by in situ polymerization or applying a preformed conductive polymer from a polymer solution or slurry. It is well known to those skilled in the art that in situ polymerization includes the polymerization of monomers in the presence of a surface on which the polymer is formed. In this case, the surface is a dielectric. Preformed conductive polymers suitable for forming the primary conductive polymer layer have a particle size of less than 20nm and preferably less than 1nm, which is considered to be undetectable, and at this point, the preformed conductive polymer refers to a soluble polymer. The primary conductive polymer layer is typically formed by multiple applications of an in situ formed layer or a conductive polymer solution or slurry. At 46, a mordant layer is formed on the primary conductive polymer layer. The mordant layer is formed by applying a solution comprising a compound defined by formula A and an optional cross-linking agent, and then drying. The solvent for the mordant layer application is not particularly limited to water, and water is an example of demonstrating the present invention. The mordant layer can be formed by a single application or continuous application of the solution. At 48, a secondary conductive polymer layer is formed on the mordant layer. The secondary conductive polymer layer is preferably formed by applying a slurry containing a conductive polymer, wherein the average particle size of the conductive polymer is at least 50nm to no more than 200nm. The secondary conductive polymer can also have a bimodal particle size distribution. Such properties of conductive polymers are described in U.S. Patents 10,650,980 and U.S. Patents 10,658,121. The secondary conductive polymer layer is preferably formed by multiple applications of the slurry. At 50, an adhesive layer is preferably formed on the secondary conductive polymer layer, wherein the adhesive layer preferably includes at least one carbon-containing layer and at least one metal-containing layer, as known in the art. At 52, the capacitor is completed, wherein the completion generally includes the connection of the cathode external terminal, the anode external terminal and the resin package. Testing and any electrical or physical processing may also be part of the finishing step.
[0028] The secondary conductive polymer layer may have a primer layer between adjacent conductive polymer sublayers to improve interlayer adhesion, the primer layer preferably comprising a crosslinking agent or a weak ionic acid. In one embodiment, the conductive polymer sublayer is deposited directly on the previously applied conductive polymer sublayer without the need for a primer in between. Primers are well known in the art, as exemplified in U.S. Patents Nos. 8,882,856, 9,761,347, 9,761,378, 10,109,428, 10,643,796, which are incorporated herein by reference. Particularly preferred primers are amine salts selected from amines and weak acids.
[0029] Particularly preferred anode materials are metals, particularly preferred metals are valve metals or conductive oxides of valve metals. Particularly preferred anodes include materials selected from niobium, aluminum, tantalum and NbO. Tantalum is the most preferred anode material. Although not limited to this, the advantages of the present invention are most easily understood by high charge density powders (e.g., 50,000CV / g or more). Below about 50,000CV / g, problems associated with power cycling are not common, so the advantages provided by the present invention are not easy to achieve. However, when the primary conductive layer is prepared only from a conductive polymer slurry, problems associated with power cycling are observed even with powders of lower charge. The types of primary conductive polymer layers and their effects on capacitance recovery and power cycling are described in U.S. Patent No. 10,879,010. The advantages of the present invention become more apparent as the charge density of the powder increases. Particularly preferred powders have a charge density of 100,000CV / g or more, preferably 200,000CV / g or more, and even more preferably from about 250,000CV / g to about 350,000CV / g.
[0030] The anode wire is embedded or attached to the anode, preferably an embedded anode wire. The structural material of the anode wire is not particularly limited, however, for ease of manufacturing, the anode wire is preferably the same as the anode material.
[0031] The dielectric and the method of forming the dielectric are not particularly limited herein. For manufacturing considerations, a particularly preferred dielectric is the oxide of the anode.
[0032] The primary conductive layer comprises a conductive polymer. The primary conductive layer is formed by in-situ polymerization of monomers, or the primary conductive layer is formed as a prepolymerized conductive polymer coating, the average particle size of the prepolymerized conductive polymer is small, less than about 20 nm, and more preferably, the primary conductive layer is formed as a soluble conductive polymer coating. The primary conductive polymer layer can also be a combination of an in-situ polymerized layer, a soluble conductive polymer layer and a prepolymerized conductive polymer slurry.
[0033] It is hypothesized that the in situ formed conductive polymer enters the interstitial portions of the porous anodized anode more efficiently, thereby forming an improved capacitor.
[0034] A soluble conductive polymer is one that is completely dissolved in a solvent or solvent mixture, with no detectable particles below about 1 nm (which is considered to be below the usual particle size detection limit).
[0035] The solvent for the soluble conductive polymer can be water, an organic solvent, or a mixture of water with a miscible solvent such as ethanol and a non-hydroxyl polar solvent such as dimethyl sulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAc), and the like.
[0036] Soluble conductive polymers are believed to impregnate the pores of the anode as effectively as conductive polymers formed by in situ methods, and better than conductive polymer dispersions with detectable particles. Both in situ conductive polymers and soluble conductive polymers do not contain polyanionic dopants, such as polystyrene sulfonic acid. In many cases, soluble conductive polymers contain self-doping functionality.
[0037] The mordant layer comprises a mordant compound defined by formula A and optionally but preferably a crosslinking agent. The mordant compound of formula A is represented by:
[0038]
[0039] Among them, R 1 -R 6 Each of which is independently selected from H and -PO(OR 7 )2, where each R 7 is independently selected from H, substituted or unsubstituted alkyl containing 1-20 carbon atoms, substituted or unsubstituted aryl containing 6-20 carbon atoms or alkylaryl containing 7-21 carbon atoms; provided that R 1 -R 6 More preferably, R 1 -R 6 At least five of them are -PO(OH)2. Most preferably, R 1 -R 6 Each of R is -PO(OH)2. 7 It may be an unsubstituted alkyl, aryl or alkylaryl group, or R 7 It may be substituted with at least one functional group selected from hydroxyl, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, anhydride or an alkali metal preferably selected from lithium, sodium and potassium.
[0040] The mordant layer optionally comprises a crosslinking agent. The crosslinking agent in the mordant layer can be crosslinked with formula A compound and conductive polymer. Crosslinking comprises using a material containing at least two crosslinkable functional groups, wherein one of the crosslinkable functional groups forms a first bond, and a second crosslinkable functional group forms a second bond, thereby forming a crosslinked molecular bridge between two molecules, oligomers, polymers or polymer parts. For purposes of the present invention, term "crosslinked crosslinking agent" is defined as the reaction product of a crosslinking agent, because the crosslinking agent does not exist as a separate compound after crosslinking. The crosslinkable functional group can form a covalent bond or an ionic bond.
[0041] Crosslinking can be carried out between the functional groups of conductive polymers or molecules, oligomers or polymers. Crosslinkable functional groups can be added to the conductive polymer layer to improve the integrity and surface coverage of the layer, or crosslinkable materials can be added to the conductive polymer layer. Once exposed to the curing conditions that are usually heat-cured, the crosslinkable molecules react with the crosslinking agent to form a strong binding interpenetrating network of covalent bonds and ionic bonds. The crosslinkable material preferably comprises two components, wherein one component is preferably a compound, oligomer or polymer with multifunctional groups or multiple reactive groups, and the multifunctional groups or multiple reactive groups are well known in the art, preferably selected from: carboxylic acid (carboxylic), hydroxyl, amine, epoxy, anhydride, isocyanate, imide, amide, carboxyl (carboxyl), carboxylic anhydride, silane, oxazoline, (meth) acrylate, vinyl, maleate, maleimide, itaconate, allyl alcohol ester, dicyclopentadienyl unsaturated substances, unsaturated C 12 -C 22 Fatty esters or amides, carboxylates, quaternary ammonium salts, polyesters, polyurethanes, polyamides, polyamines, polyimides, silicone polyesters, hydroxy-functional silicones, hydroxyethylcellulose, polyvinyl alcohol, phenolic, epoxy, butyral, copolymers of these substances or mixtures of these multifunctional polymers, such as epoxy / amine, epoxy / anhydride, isocyanate / amine, isocyanate / alcohol, unsaturated polyesters, vinyl esters, unsaturated polyester and vinyl ester mixtures, unsaturated polyester / urethane hybrid resins, polyurethane-urea, reactive dicyclopentadiene resins or reactive polyamides. The oligomers or polymers with multifunctional or multiple reactive groups preferably contain at least one carboxylic acid group and at least one hydroxyl functional group. Particularly preferred oligomers or polymers with multifunctional reactive groups are polyesters containing carboxylic acid and hydroxyl functional groups. In addition to oligomers or polymers, particles with surface functional groups can also participate in crosslinking.
[0042] The crosslinking agent includes silane compounds and epoxy compounds. Particularly preferred crosslinking agents include melamine, isocyanate, epoxy, hexamethoxymelamine, glyoxal, furfural, melamine formaldehyde condensate, divinyl sulfone and epoxy compounds.
[0043] Organofunctional silanes and organic compounds having more than one crosslinking group, especially more than one epoxy group, are particularly suitable for use as crosslinkers according to the invention, especially when used in combination.
[0044] Exemplary organofunctional silanes are defined by the formula:
[0045] XR1Si(R3) 3-n (R2) n ,
[0046] Wherein X is an organic functional group, such as amino, epoxy, anhydride, hydroxyl, mercapto, sulfonate, carboxylate, phosphonate, halogen, vinyl, methacryloxy, ester, alkyl, etc.; R1 is aryl or alkyl (CH2) m , wherein m can be 0-14; R2 is independently a hydrolyzable functional group, such as alkoxy, acyloxy, halogen, amine or their hydrolysis products; R3 is independently an alkyl functional group containing 1-6 carbons; n is 1-3.
[0047] The organofunctional silane can also be dipodal, defined by the formula: Y(Si(R3) 3-n (R2) n )2
[0048] Wherein Y is any organic group containing reactive or non-reactive functional groups, such as alkyl, aryl, sulfide or melamine; R3, R2 and n are defined above. The organofunctional silane can also be a multifunctional silane or a polymeric silane, such as a polybutadiene-modified silane or a polyamine-modified silane.
[0049] Examples of organofunctional silanes include 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltriethoxysilane, aminopropylsilanetriol, (triethoxysilyl)propylsuccinic anhydride, 3-mercaptopropyltrimethoxysilane, vinyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-trihydroxysilyl-1-propanesulfonic acid, octyltriethoxysilane, bis(triethoxysilyl)octane, etc. The examples are provided to illustrate the invention and should not be considered conclusive. Examples of organofunctional silanes include 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltriethoxysilane, aminopropylsilanetriol, (triethoxysilyl)propylsuccinic anhydride, 3-mercaptopropyltrimethoxysilane, vinyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-trihydroxysilyl-1-propanesulfonic acid, octyltriethoxysilane, bis(triethoxysilyl)octane, etc. The examples are provided to illustrate the invention and should not be considered conclusive.
[0050] Particularly preferred organofunctional silanes are glycidoxysilanes defined by the formula:
[0051]
[0052] Where R 8 is an alkyl group containing 1 to 14 carbon atoms, more preferably selected from methyl, ethyl and propyl; and each R 9 is independently an alkyl or substituted alkyl group containing 1 to 6 carbon atoms.
[0053] A particularly preferred glycidoxysilane is 3-glycidoxypropyltrimethoxysilane defined by the formula:
[0054]
[0055] For convenience, it is referred to herein as "Silane A".
[0056] A crosslinking agent containing at least two epoxy groups is referred to herein as an epoxy crosslinking compound and is defined by the following formula:
[0057]
[0058] Wherein, X is: an alkyl or substituted alkyl containing 0-14 carbons, preferably 0-6 carbons, an aryl or substituted aryl, a vinyl ether or substituted vinyl ether, a polyethylene ether or substituted polyethylene ether having 2-20 vinyl ether groups, or a combination thereof. A particularly preferred substituent is an epoxy group.
[0059] Examples of epoxy crosslinking compounds having more than one epoxy group include ethylene glycol diglycidyl ether (EGDGE), propylene glycol diglycidyl ether (PGDGE), 1,4-butanediol diglycidyl ether (BDDGE), pentanediol diglycidyl ether, hexanediol diglycidyl ether, cyclohexanedimethanol diglycidyl ether, resorcinol glycidyl ether, glycerol diglycidyl ether (GDGE), glycerol polyglycidyl ether, diglycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, sorbitol diglycidyl ether, and 1,4-butanediol diglycidyl ether. Glyceryl ether (sorbitol-DGE), sorbitol polyglycidyl ether, polyethylene glycol diglycidyl ether (PEGDGE), polypropylene glycol diglycidyl ether, polytetramethylene glycol diglycidyl ether, di(2,3-epoxypropyl) ether, 1,3-butadiene diepoxide, 1,5-hexadiene diepoxide, 1,2,7,8-diepoxyoctane, 1,2,5,6-diepoxycyclooctane, 4-vinylcyclohexene diepoxide, bisphenol A diglycidyl ether, maleimide-epoxy compounds, etc.
[0060] Preferred epoxy crosslinking compounds are glycidyl ethers, which are defined by the formula:
[0061]
[0062] Where R 10is: an alkyl or substituted alkyl containing 1 to 14 carbon atoms, preferably 2 to 6 carbon atoms, a vinyl ether or a polyethylene ether having 2 to 20 vinyl ether groups, selected from hydroxyl, and—(CH2OH) x An alkyl group substituted with CH2OH (wherein x is 1-14).
[0063] Particularly preferred glycidyl ethers are:
[0064]
[0065] EGDGE: ethylene glycol diglycidyl ether;
[0066]
[0067] Where n is an integer from 1 to 220,
[0068] PEGDGE: polyethylene glycol diglycidyl ether;
[0069]
[0070] BDDGE: 1,4-butanediol diglycidyl ether;
[0071]
[0072] One of the R 11 is H, and each of the other R 11 for
[0073] GDGE: glycerol diglycidyl ether;
[0074]
[0075] Sorbitol-DGE: sorbitan diglycidyl ether.
[0076] Mixtures of cross-linking agents may be used.
[0077] The secondary conductive polymer layer is formed from a slurry comprising a prepolymerized polymer of polythiophene and an optional dopant, such as styrene sulfonic acid or a polymer comprising styrene sulfonic acid groups. A preferred polymerization process uses a stator screen that provides a uniform droplet size such that the average polymer particle size is at least about 50 nm to no more than about 200 nm, more preferably 150 nm, and even more preferably less than about 100 nm.
[0078] The preferred polythiophene monomers for polymerization are of formula B:
[0079]
[0080] in:
[0081] R 1 and R 2 are independently linear or branched C1-C 16 Alkyl, C2-C 18 Alkoxyalkyl, C3-C8 cycloalkyl, phenyl or benzyl, which is unsubstituted or substituted by C1-C6 alkyl, C1-C6 alkoxy, halogen or OR 3 Replacement; or R 1 and R 2 Together, they are linear C1-C6 alkylene groups, which are unsubstituted or substituted with the following functional groups: C1-C6 alkyl, C1-C6 alkoxy, halogen, C3-C8 cycloalkyl, phenyl, benzyl, C1-C4 alkylphenyl, C1-C4 alkoxyphenyl, halogenated phenyl, C1-C4 alkylbenzyl, C1-C4 alkoxybenzyl or halogenated benzyl, a five-membered, six-membered or seven-membered heterocyclic structure containing two oxygen elements. 3 is: hydrogen, unsubstituted or C1-C6 alkyl-substituted linear or branched C 1- C 16 Alkyl or C2-C 18 Alkoxyalkyl, C3-C8 cycloalkyl, phenyl or benzyl. X is S.
[0082] n represents a number which makes the compound of formula B a polymer having a certain molecular weight range; generally, n is an integer from 2 to an integer sufficient to give an average molecular weight of about 500,000.
[0083] Preferably, R of formula B is selected 1 and R 2 to prohibit polymerization at the β position of the ring, since it is most preferred to allow only α position polymerization. More preferably, R 1 and R 2 is not hydrogen, more preferably, R 1 and R 2 It is an α-director, and ether bonds are preferred over alkyl bonds. 1 and R 2 Smaller to avoid space interference.
[0084] In a particularly preferred embodiment, R of Formula B 1 and R 2 Together for -O-(CHR 4 )mO, wherein m is an integer from 1 to 5, most preferably 2; each R 4 are independently selected from: hydrogen; linear or branched C1 to C 18 Alkyl, C5 to C 12 Cycloalkyl, C6 to C 14 Aryl, C7 to C 18Aralkyl or C1 to C4 hydroxyalkyl, optionally substituted with a functional group selected from carboxylic acid, hydroxyl, amine, substituted amine, olefin, acrylate, thiol, alkyne, azide, sulfate, sulfonate, sulfonic acid, imide, amide, epoxy, anhydride, silane and phosphate; or hydroxyl; or R 4 Selected from -(CHR 5 ) a -R 16 、-O(CHR 5 ) a R 16 、-CH2O(CHR 5 ) a R 16 、-CH2O(CH2CHR 5 O) a R 16 ; or R 4 R is a functional group selected from hydroxyl, carboxyl, amine, epoxy, amide, imide, anhydride, hydroxymethyl, olefin, thiol, alkyne, azide, sulfonic acid, benzenesulfonic acid sulfate, SO3M, anhydride, silane, acrylate and phosphate. 5 is H; or an alkyl chain containing 1-5 carbons, optionally substituted with a functional group selected from carboxylic acid, hydroxyl, amine, olefin, thiol, alkyne, azide, epoxy, acrylate and anhydride. 16 is H; -SO3M; or an alkyl chain containing 1 to 5 carbons, optionally substituted with a functional group selected from carboxylic acid, hydroxyl, amine, substituted amine, olefin, thiol, alkyne, azide, amide, imide, sulfate, SO3M, amide, epoxy, anhydride, silane, acrylate and phosphate. a is an integer from 0 to 10. M is H; or a cation, preferably a cation selected from ammonia, sodium or potassium.
[0085] A particularly preferred polymer is 3,4-polyethylenedioxythiophene (PEDOT), which is prepared from the monomer 3,4-ethylenedioxythiophene (EDOT).
[0086] Particularly preferred conductive polymers include poly(3,4-ethylenedioxythiophene), poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)-1-butane-sulfonic acid, salt), poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)-1-propane-sulfonic acid, salt), poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)-1-methyl-1-propane-sulfonic acid, salt), poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)-1-methyl-1-propane-sulfonic acid, salt), poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)-1-methyl-1-propane-sulfonic acid, salt), [3,4-b][1,4]dioxin-2-yl)methoxy alcohol, poly(N-methylpyrrole), poly(3-methylpyrrole), poly(3-octylpyrrole), poly(3-decylpyrrole), poly(3-dodecylpyrrole), poly(3,4-dimethylpyrrole), poly(3,4-dibutylpyrrole), poly(3-carboxypyrrole), poly(3-methyl-4-carboxypyrrole), poly(3-methyl-4-carboxyethylpyrrole), poly(3-methyl-4-carboxybutylpyrrole), poly(3-hydroxypyrrole), poly(3-methoxypyrrole), polythiophene, poly(3-methylthiophene) , poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), ... thiophene), poly(3-octadecyloxythiophene), poly(3,4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butenedioxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), poly(3-methyl-4-carboxybutylthiophene), polyaniline, poly(2-methylaniline), poly(3-isobutylaniline), poly(2-aniline sulfonate), poly(3-aniline sulfonate), and the like.
[0087] Particularly suitable polymers or copolymers are selected from poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)-1-butanesulfonic acid, salt), poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)-1-methyl-1-propanesulfonic acid, salt), poly(N-methylpyrrole), poly(3-methylthiophene), poly(3-methoxythiophene) and poly(3,4-ethylenedioxythiophene).
[0088] The insulating resin is not particularly limited herein, and any non-conductive compatible resin is suitable for use in the demonstration of the present invention. If the electrolytic capacitor is embedded or encapsulated, the resin is optional.
[0089] Example
[0090] The ESR (equivalent series resistance) of the capacitors was measured at 100kHz using an Agilent E4980A precision LCR tester. The power cycling test (surge voltage) was performed at an ambient temperature of 85°C with the rated voltage turned on for 5 seconds and then turned off for 5 seconds. The voltage on / off cycle was repeated 60,000 times. The capacitance of the components was tested before and after the power cycle, and the percentage of capacitance change was calculated.
[0091] Comparative Example 1 :
[0092] A series of tantalum anodes (100 microfarads, 35V) were prepared. Tantalum was anodized to form a dielectric on the tantalum anode. A silane-based organic compound was applied to the dielectric. The formed anode was immersed in the oxidant iron toluenesulfonate, then immersed in the EDOT monomer, dried and cleaned. This process was repeated several times to form a PEDOT film in the anode pores. A conductive polymer dispersion containing an epoxy compound and a silane compound was applied to form a subsequent polymer layer. After drying, layers of amine salts and a second conductive polymer dispersion were applied alternately and repeated 4-5 more times. The anode with the conductive polymer layer was cleaned and dried, and then a graphite layer and a silver layer were coated in sequence to produce a solid electrolytic capacitor. The components were assembled and packaged. The capacitance and ESR were measured on the packaged components.
[0093] Comparative Example 2 :
[0094] A series of tantalum anodes (100 microfarads, 35V) were prepared. Tantalum was anodized to form a dielectric on the tantalum anode. A silane-based organic compound was applied to the dielectric. The formed anode was immersed in the oxidant iron toluenesulfonate, then immersed in the EDOT monomer, dried and cleaned. This process was repeated several times to form a PEDOT film in the anode pores. A cross-linking agent selected from a difunctional epoxy compound was applied to the surface of the PEDOT film thus formed. A conductive polymer dispersion containing an epoxy compound and a silane compound was applied to form a subsequent polymer layer. After drying, layers of amine salts and a second conductive polymer dispersion were applied alternately and repeated 4-5 more times. The anode with the conductive polymer layer was cleaned and dried, and then a graphite layer and a silver layer were coated in sequence to produce a solid electrolytic capacitor. The components were assembled and packaged. The capacitance and ESR of the packaged components were measured.
[0095] Comparative Example 3 :
[0096] A series of tantalum anodes (100 microfarads, 35V) were prepared. Tantalum was anodized to form a dielectric on the tantalum anode. A silane-based organic compound was applied to the dielectric. The formed anode was immersed in the oxidant iron toluenesulfonate, then immersed in the EDOT monomer, dried and cleaned. This process was repeated several times to form a PEDOT film in the anode pores. A coating prepared from a difunctional epoxy crosslinker and polyethylene oxide was applied to the surface of the PEDOT film thus formed. A conductive polymer dispersion containing an epoxy compound and a silane compound was applied to form a subsequent polymer layer. After drying, layers of amine salts and a second conductive polymer dispersion were applied alternately and repeated 4-5 more times. The anode with the conductive polymer layer was cleaned and dried, and then a graphite layer and a silver layer were coated in sequence to produce a solid electrolytic capacitor. The components were assembled and packaged. The capacitance and ESR of the packaged components were measured.
[0097] Embodiment 1 of the present invention :
[0098] A series of tantalum anodes (100 microfarads, 35V) were prepared. Tantalum was anodized to form a dielectric on the tantalum anode. A silane-based organic compound was applied to the dielectric. The formed anode was immersed in the oxidant iron toluenesulfonate, then immersed in the EDOT monomer, dried and cleaned. This process was repeated several times to form a PEDOT film in the anode pores. A coating containing inositol hexaphosphate (called phytic acid) was applied to the PEDOT film. A conductive polymer dispersion containing an epoxy compound and a silane compound was applied to form a subsequent polymer layer. After drying, layers of amine salts and a second conductive polymer dispersion were applied alternately and repeated 4-5 more times. The anode with the conductive polymer layer was cleaned and dried, and then a graphite layer and a silver layer were coated in sequence to produce a solid electrolytic capacitor. The components were assembled and packaged. The capacitance and ESR were measured on the packaged components.
[0099] Embodiment 2 of the present invention :
[0100] A series of tantalum anodes (100 microfarads, 35V) were prepared. Tantalum was anodized to form a dielectric on the tantalum anode. A silane-based organic compound was applied to the dielectric. The formed anode was immersed in the oxidant iron toluenesulfonate, then immersed in the EDOT monomer, dried and cleaned. This process was repeated several times to form a PEDOT film in the anode pores. A coating containing phytic acid and a difunctional crosslinker was applied to the PEDOT film. A conductive polymer dispersion containing an epoxy compound and a silane compound was applied to form a subsequent polymer layer. After drying, layers of amine salts and a second conductive polymer dispersion were applied alternately and repeated 4-5 more times. The anode with the conductive polymer layer was cleaned and dried, and then a graphite layer and a silver layer were coated in sequence to produce a solid electrolytic capacitor. The components were assembled and packaged. The capacitance and ESR of the packaged components were measured.
[0101]
[0102] Embodiments of the present invention show the following advantages: low initial ESR, significant improvement in capacitance loss and ESR after 50,000 power cycles. As shown, the capacitor of the present invention has less than 10% and more preferably less than 5% capacitance loss after 50,000 power cycles relative to the capacitance before power cycling. In addition to improved power cycling properties, the method of the present invention also shows improved ESR stability, as well as improved abnormal charge current properties. Abnormal charge current in solid electrolytic capacitors is described in other documents. (Y. Freeman et al., 2013ECS J. Solid State Sci. Technol. 2N197, Chacko et al., 9,793,058).
[0103] The present invention has been described with reference to preferred embodiments but is not limited thereto. Additional embodiments will occur to those skilled in the art as described and set forth in the appended claims.
Claims
1. An electrolytic capacitor, comprising: an anode including a dielectric layer on the anode; a primary conductive polymer layer on said dielectric layer; A mordant layer on the primary conductive polymer layer, wherein the mordant layer comprises a mordant compound of formula A: in: R 1 -R 6 Each of which is independently selected from H and -PO(OR 7 )2, where each R 7 is independently selected from H, substituted or unsubstituted alkyl containing 1-20 carbon atoms, substituted or unsubstituted aryl containing 6-20 carbon atoms or alkylaryl containing 7-21 carbon atoms; provided that R 1 -R 6 At least one of them is -PO(OH)2; and a secondary conductive polymer layer on the mordant layer; The mordant layer further comprises a cross-linking agent.
2. The electrolytic capacitor according to claim 1, wherein the R 1 -R 6 At least two of them are -PO(OH)2.
3. The electrolytic capacitor according to claim 2, wherein the R 1 -R 6 At least three of them are -PO(OH)2.
4. The electrolytic capacitor according to claim 3, wherein the R 1 -R 6 At least four of them are -PO(OH)2.
5. The electrolytic capacitor according to claim 4, wherein the R 1 -R 6 At least five of them are -PO(OH)2.
6. The electrolytic capacitor according to claim 5, wherein the R 1 -R 6 Each of them is -PO(OH)2.
7. The electrolytic capacitor according to claim 1, wherein R 7 The compound is substituted with at least one functional group selected from the group consisting of hydroxyl, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, anhydride and alkali metal.
8. The electrolytic capacitor of claim 1, wherein the anode comprises a valve metal.
9. The electrolytic capacitor of claim 8, wherein the valve metal is selected from the group consisting of aluminum, tantalum, and niobium.
10. The electrolytic capacitor of claim 1 wherein the anode comprises a powder having a charge density of at least 50,000 CV / g.
11. The electrolytic capacitor of claim 10, wherein the anode comprises a powder having a charge density of at least 100,000 CV / g.
12. The electrolytic capacitor of claim 11 wherein the anode comprises a powder having a charge density of at least 200,000 CV / g.
13. The electrolytic capacitor of claim 1, having a capacitance loss of less than 10% after 50,000 power cycles relative to the capacitance before the power cycles.
14. The electrolytic capacitor of claim 13, wherein the capacitance loss after 50,000 power cycles relative to the capacitance before the power cycles is less than 5%.
15. The electrolytic capacitor of claim 1, wherein the primary conductive polymer layer comprises a polymer layer selected from the group consisting of a polymer layer formed by in-situ polymerization and a polymer layer formed by a prepolymerized polymer having a particle size of less than 20 nm.
16. The electrolytic capacitor of claim 15, wherein the prepolymerized polymer has a particle size of less than 1 nm.
17. The electrolytic capacitor of claim 16, wherein the prepolymerized polymer is a soluble polymer.
18. The electrolytic capacitor of claim 1, wherein the cross-linking agent has a cross-linking functional group selected from the group consisting of carboxylic acid, hydroxyl, amine, epoxy, anhydride, isocyanate, imide, amide, carboxyl, carboxylic anhydride, silane, oxazoline, (meth)acrylate, vinyl, maleate, maleimide, itaconate, allyl alcohol ester, dicyclopentadienyl unsaturated, unsaturated C 12 -C 22 Fatty esters, unsaturated C 12 -C 22 Fatty amides, carboxylates, quaternary ammonium salts, polyesters, polyurethanes, polyamides, polyamines, polyimides, silicone polyesters, hydroxy-functional silicones, hydroxyethyl cellulose, polyvinyl alcohol, phenolic, butyral and mixtures thereof.
19. The electrolytic capacitor according to claim 1, wherein the cross-linking agent contains at least an amine group.
20. The electrolytic capacitor of claim 1, wherein the cross-linking agent contains at least one group selected from the group consisting of melamine, isocyanate, epoxy, hexamethoxymelamine, glyoxal, furfural, melamine formaldehyde condensate, divinyl sulfone and epoxy compounds.
21. The electrolytic capacitor of claim 1, wherein the cross-linking agent is an organofunctional silane defined by the formula: XR1Si(R3) 3-n (R2) n , in: X is an organic functional group selected from amino, epoxy, anhydride, hydroxyl, mercapto, sulfonate, carboxylate, phosphonate, halogen, vinyl, methacryloxy, ester and alkyl; R1 is aryl or alkyl (CH2) m , where m is 0 to 14; R2 is independently a hydrolyzable functional group selected from alkoxy, acyloxy, halogen, amine or their hydrolysis products; R3 is independently an alkyl functional group containing 1 to 6 carbon atoms; and n is 1-3.
22. The electrolytic capacitor of claim 1, wherein the cross-linking agent is defined by the formula: Y(Si(R3) 3-n (R2) n )2, in: Y is an organic group containing a reactive or non-reactive functional group; R2 is independently a hydrolyzable functional group selected from alkoxy, acyloxy, halogen, amine or their hydrolysis products; R3 is independently an alkyl functional group containing 1 to 6 carbon atoms; and n is 1-3.
23. The electrolytic capacitor of claim 1, wherein the cross-linking agent is selected from the group consisting of 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltriethoxysilane, aminopropylsilanetriol, (triethoxysilyl)propylsuccinic anhydride, 3-mercaptopropyltrimethoxysilane, vinyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-trihydroxysilyl-1-propanesulfonic acid, octyltriethoxysilane and bis(triethoxysilyl)octane.
24. The electrolytic capacitor of claim 1, wherein the cross-linking agent is defined by the formula: Where R 8 is an alkyl group containing 1 to 14 carbon atoms; and each R 9 is independently an alkyl or substituted alkyl group containing 1 to 6 carbon atoms.
25. The electrolytic capacitor according to claim 24, wherein the R 8 Selected from methyl, ethyl and propyl.
26. The electrolytic capacitor of claim 1, wherein the cross-linking agent is defined by the formula: in, X is: an alkyl group or a substituted alkyl group containing 0 to 14 carbon atoms, an aryl group or a substituted aryl group, a vinyl ether or a substituted vinyl ether, a polyethylene ether or a substituted polyethylene ether having 2 to 20 vinyl ether groups, or a combination thereof.
27. The electrolytic capacitor of claim 1, wherein the cross-linking agent is selected from the group consisting of ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, pentanediol diglycidyl ether, hexanediol diglycidyl ether, cyclohexanedimethanol diglycidyl ether, resorcinol glycidyl ether, glycerol diglycidyl ether, glycerol polyglycidyl ether, diglycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, sorbitol diglycidyl ether, Water glyceryl ether, sorbitol polyglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, polytetramethylene glycol diglycidyl ether, di(2,3-epoxypropyl) ether, 1,3-butadiene diepoxide, 1,5-hexadiene diepoxide, 1,2,7,8-diepoxyoctane, 1,2,5,6-diepoxycyclooctane, 4-vinylcyclohexene diepoxide, bisphenol A diglycidyl ether and maleimide-epoxide compounds.
28. The electrolytic capacitor of claim 1, wherein the cross-linking agent is defined by the formula: Where R 10 is: an alkyl group or a substituted alkyl group containing 1 to 14 carbon atoms; a vinyl ether or a polyethylene ether having 2 to 20 vinyl ether groups; a hydroxyl group, and -(CH2OH) x An alkyl group substituted with CH2OH, wherein x is 1-14.
29. The electrolytic capacitor of claim 1, wherein the cross-linking agent is selected from: wherein n is an integer from 1 to 220; One of the R 11 is H, and each of the other R 11 for and 30. The electrolytic capacitor of claim 1 wherein the secondary conductive polymer layer comprises a primer.
31. The electrolytic capacitor of claim 1 , wherein at least one of the primary conductive polymer layer or the secondary conductive polymer layer comprises a polymer defined by Formula B: in: R 1 and R 2 are independently linear or branched C1-C 16 Alkyl or C2-C 18 Alkoxyalkyl, C3-C8 cycloalkyl, phenyl or benzyl, which is unsubstituted or substituted by C1-C6 alkyl, C1-C6 alkoxy, halogen or OR 3 replace; or R 1 and R 2 Together, they are linear C1-C6 alkylene groups which are unsubstituted or substituted with the following functional groups: C1-C6 alkyl, C1-C6 alkoxy, halogen, C3-C8 cycloalkyl, phenyl, benzyl, C1-C4 alkylphenyl, C1-C4 alkoxyphenyl, halophenyl, C1-C4 alkylbenzyl, C1-C4 alkoxybenzyl, halobenzyl, or a five-membered, six-membered, or seven-membered heterocyclic structure containing two oxygen elements; R 3 is: hydrogen, unsubstituted or C1-C6 alkyl-substituted linear or branched C 1- C 16 Alkyl, C2-C 18 Alkoxyalkyl, C3-C8 cycloalkyl, phenyl or benzyl; X is S; and n is an integer from 2 to a value sufficient to give a molecular weight of about 500,000.
32. The electrolytic capacitor according to claim 31, wherein R in Formula B 1 and R 2 Together for -O-(CHR 4 )mO, where: m is an integer from 1 to 5; R 4 are independently selected from hydrogen; linear or branched C1 to C 18 Alkyl, C5 to C 12 Cycloalkyl, C6 to C 14 Aryl, C7 to C 18 Aralkyl or C1 to C4 hydroxyalkyl, which is unsubstituted or substituted with a functional group selected from the group consisting of carboxylic acid, hydroxyl, amine, olefin, acrylate, thiol, alkyne, azide, sulfate, sulfonate, sulfonic acid, imide, amide, epoxy, anhydride, silane and phosphate; hydroxyl; -(CHR 5 ) a -R 16 ;-O(CHR 5 ) a R 16 ; -CH2O(CHR 5 ) a R 16 ; or -CH2O(CH2CHR 5 O) a R 16 ;or R 4 is a functional group selected from the group consisting of hydroxyl, carboxyl, amine, epoxy, amide, imide, anhydride, hydroxymethyl, olefin, thiol, alkyne, azide, sulfonic acid, benzenesulfonic acid sulfate, SO3M, anhydride, silane, acrylate and phosphate; R 5 is H or an alkyl chain containing 1 to 5 carbons, which is unsubstituted or substituted with a functional group selected from carboxylic acid, hydroxyl, amine, olefin, thiol, alkyne, azide, epoxy, acrylate and anhydride; R 16 is H, -SO3M or an alkyl chain containing 1 to 5 carbons, which is unsubstituted or substituted with a functional group selected from carboxylic acid, hydroxyl, amine, olefin, thiol, alkyne, azide, amide, imide, sulfate, -SO3M, amide, epoxy, anhydride, silane, acrylate and phosphate; a is an integer from 0 to 10; and M is H or a cation selected from ammonia, sodium or potassium.
33. The electrolytic capacitor of claim 31 , wherein the polymer is 3,4-polyethylenedioxythiophene.
34. The electrolytic capacitor of claim 31, wherein the polymer is selected from the group consisting of poly(3,4-ethylenedioxythiophene), poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)-1-butane-sulfonic acid, salt), poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)-1-propane-sulfonic acid, salt), poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)-1-methyl-1-propane-sulfonic acid, salt), Poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy alcohol, poly(N-methylpyrrole), poly(3-methylpyrrole), poly(3-octylpyrrole), poly(3-decylpyrrole), poly(3-dodecylpyrrole), poly(3,4-dimethylpyrrole), poly(3,4-dibutylpyrrole), poly(3-carboxypyrrole), poly(3-methyl-4-carboxypyrrole), poly(3-methyl-4-carboxyethylpyrrole), poly(3-methyl-4-carboxybutylpyrrole), poly(3-hydroxypyrrole), poly(3-methoxypyrrole), polythiophene, Poly(3-methylthiophene), poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxy ... 4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butenedioxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), poly(3-methyl-4-carboxybutylthiophene), polyaniline, poly(2-methylaniline), poly(3-isobutylaniline), poly(2-aniline sulfonate), and poly(3-aniline sulfonate).
35. The electrolytic capacitor of claim 31 , wherein the polymer is selected from the group consisting of poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)-1-butanesulfonic acid, salt), poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)-1-methyl-1-propanesulfonic acid, salt), poly(N-methylpyrrole), poly(3-methylthiophene), poly(3-methoxythiophene), and poly(3,4-ethylenedioxythiophene).
36. A method of forming an electrolytic capacitor, comprising: forming an anode; forming a dielectric on the anode; forming a primary conductive polymer layer on the dielectric; A mordant layer is formed on the primary conductive polymer layer, wherein the mordant layer comprises a mordant compound of formula A: Among them, R 1 -R 6 Each of which is independently selected from H and -PO(OR 7 )2, where each R 7 is independently selected from H, substituted or unsubstituted alkyl containing 1-20 carbon atoms, substituted or unsubstituted aryl containing 6-20 carbon atoms or alkylaryl containing 7-21 carbon atoms; provided that R 1 -R 6 At least one of them is -PO(OH)2; and forming a secondary conductive polymer layer on the mordant layer; The forming of the mordant layer further comprises adding a cross-linking agent.
37. The method of forming an electrolytic capacitor according to claim 36, wherein the R 1 -R 6 At least two of them are -PO(OH)2.
38. The method of forming an electrolytic capacitor according to claim 37, wherein the R 1 -R 6 At least three of them are -PO(OH)2.
39. The method of forming an electrolytic capacitor according to claim 38, wherein the R 1 -R 6 At least four of them are -PO(OH)2.
40. The method of forming an electrolytic capacitor of claim 39, wherein said R 1 -R 6 At least five of them are -PO(OH)2.
41. The method of forming an electrolytic capacitor of claim 40, wherein said R 1 -R 6 Each of them is -PO(OH)2.
42. The method of forming an electrolytic capacitor of claim 36, wherein R 7 The compound is substituted with at least one functional group selected from the group consisting of hydroxyl, carboxyl, amine, epoxy, silane, amide, imide, thiol, olefin, alkyne, phosphate, azide, acrylate, anhydride and alkali metal.
43. The method for forming an electrolytic capacitor of claim 36 wherein said anode comprises a valve metal.
44. The method for forming an electrolytic capacitor of claim 43 wherein the valve metal is selected from the group consisting of aluminum, tantalum, and niobium.
45. The method for forming an electrolytic capacitor of claim 36 wherein said anode comprises a powder having a charge density of at least 50,000 CV / g.
46. The method for forming an electrolytic capacitor of claim 45 wherein said anode comprises a powder having a charge density of at least 100,000 CV / g.
47. The method for forming an electrolytic capacitor of claim 46 wherein said anode comprises a powder having a charge density of at least 200,000 CV / g.
48. The method of forming an electrolytic capacitor of claim 36 wherein the capacitor has a capacitance loss of less than 10% after 50,000 power cycles relative to the capacitance before power cycling.
49. The method of forming an electrolytic capacitor of claim 48 wherein the capacitor has a capacitance loss of less than 5% after 50,000 power cycles relative to the capacitance before power cycling.
50. The method for forming an electrolytic capacitor of claim 36, wherein said forming a primary conductive polymer layer comprises in-situ polymerization.
51. The method of forming an electrolytic capacitor of claim 36, wherein said forming a primary conductive polymer layer comprises applying a prepolymerized polymer having a particle size less than 20 nm.
52. The method for forming an electrolytic capacitor of claim 51 wherein the prepolymerized polymer has a particle size of less than 1 nm.
53. The method for forming an electrolytic capacitor of claim 52 wherein the pre-polymerized polymer is a soluble polymer.
54. The method of forming an electrolytic capacitor of claim 36, wherein the crosslinking agent has a crosslinkable functional group selected from the group consisting of carboxylic acid, hydroxyl, amine, epoxy, anhydride, isocyanate, imide, amide, carboxyl, carboxylic anhydride, silane, oxazoline, (meth)acrylate, vinyl, maleate, maleimide, itaconate, allyl alcohol ester, dicyclopentadienyl unsaturated, unsaturated C 12 -C 22 Fatty esters, unsaturated C 12 -C 22 Fatty amides, carboxylates, quaternary ammonium salts, polyesters, polyurethanes, polyamides, polyamines, polyimides, silicone polyesters, hydroxy functional silicones, hydroxyethyl cellulose, polyvinyl alcohol, phenolic, epoxy, butyral and mixtures thereof.
55. The method for forming an electrolytic capacitor of claim 36 wherein the cross-linking agent contains at least an amine group.
56. The method for forming an electrolytic capacitor of claim 36, wherein the crosslinking agent contains at least one group selected from the group consisting of melamine, isocyanate, epoxy, hexamethoxymelamine, glyoxal, furfural, melamine formaldehyde condensate, divinyl sulfone, and epoxy compounds.
57. The method for forming an electrolytic capacitor of claim 36, wherein the crosslinking agent is an organofunctional silane defined by the formula: XR1Si(R3) 3-n (R2) n , in: X is an organic functional group selected from amino, epoxy, anhydride, hydroxyl, mercapto, sulfonate, carboxylate, phosphonate, halogen, vinyl, methacryloxy, ester and alkyl; R1 is aryl or alkyl (CH2) m , where m is 0 to 14; R2 is independently a hydrolyzable functional group selected from alkoxy, acyloxy, halogen, amine or their hydrolysis products; R3 is independently an alkyl functional group containing 1 to 6 carbon atoms; and n is 1 to 3.
58. The method for forming an electrolytic capacitor of claim 36, wherein the cross-linking agent is defined by the formula: Y(Si(R3) 3-n (R2) n )2, in: Y is an organic group containing a reactive or non-reactive functional group; R2 is independently a hydrolyzable functional group selected from alkoxy, acyloxy, halogen, amine or their hydrolysis products; R3 is independently an alkyl functional group containing 1 to 6 carbon atoms; and n is 1 to 3.
59. The method for forming an electrolytic capacitor of claim 36 wherein the crosslinking agent is selected from the group consisting of 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltriethoxysilane, aminopropylsilanetriol, (triethoxysilyl)propylsuccinic anhydride, 3-mercaptopropyltrimethoxysilane, vinyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-trihydroxysilyl-1-propanesulfonic acid, octyltriethoxysilane, and bis(triethoxysilyl)octane.
60. The method for forming an electrolytic capacitor of claim 36, wherein the crosslinking agent is defined by the formula: Where R 8 is an alkyl group containing 1 to 14 carbon atoms; and each R 9 is independently an alkyl or substituted alkyl group containing 1 to 6 carbon atoms.
61. The method of forming an electrolytic capacitor of claim 60, wherein said R 8 Selected from methyl, ethyl and propyl.
62. The method for forming an electrolytic capacitor of claim 36, wherein the crosslinking agent is defined by the formula: in, X is: an alkyl group or a substituted alkyl group containing 0 to 14 carbon atoms, an aryl group or a substituted aryl group, a vinyl ether or a substituted vinyl ether, a polyethylene ether or a substituted polyethylene ether having 2 to 20 vinyl ether groups, or a combination thereof.
63. The method of forming an electrolytic capacitor of claim 36, wherein the crosslinking agent is selected from the group consisting of ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, pentanediol diglycidyl ether, hexanediol diglycidyl ether, cyclohexanedimethanol diglycidyl ether, resorcinol glycidyl ether, glycerol diglycidyl ether, glycerol polyglycidyl ether, diglycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, sorbitol diglycidyl ether, Glycidyl ethers, sorbitol polyglycidyl ethers, polyethylene glycol diglycidyl ethers, polypropylene glycol diglycidyl ethers, polytetramethylene glycol diglycidyl ethers, bis(2,3-epoxypropyl) ethers, 1,3-butadiene diepoxide, 1,5-hexadiene diepoxide, 1,2,7,8-diepoxyoctane, 1,2,5,6-diepoxycyclooctane, 4-vinylcyclohexene diepoxide, bisphenol A diglycidyl ether, and maleimide-epoxides.
64. The method for forming an electrolytic capacitor of claim 36, wherein the cross-linking agent is defined by the formula: Where R 10 is: an alkyl group or a substituted alkyl group containing 1 to 14 carbon atoms; a vinyl ether or a polyethylene ether having 2 to 20 vinyl ether groups; a hydroxyl group, and -(CH2OH) x An alkyl group substituted with CH2OH, wherein x is 1-14.
65. The method for forming an electrolytic capacitor of claim 36 wherein the crosslinking agent is selected from: Wherein n is an integer from 1 to 220; One of the R 11 is H, and each of the other R 11 for and 66. The method for forming an electrolytic capacitor of claim 36 wherein said secondary conductive polymer layer comprises the addition of a primer.
67. The method for forming an electrolytic capacitor of claim 66 wherein said primer is between adjacent conductive polymer sub-layers.
68. The method of forming an electrolytic capacitor of claim 36 wherein at least one of the primary conductive polymer layer or the secondary conductive polymer layer comprises a polymer defined by Formula B: in: R 1 and R 2 are independently linear or branched C1-C 16 Alkyl or C2-C 18 Alkoxyalkyl, C3-C8 cycloalkyl, phenyl or benzyl, which is unsubstituted or substituted by C1-C6 alkyl, C1-C6 alkoxy, halogen or OR 3 replace; or R 1 and R 2 Together, they are linear C1-C6 alkylene groups which are unsubstituted or substituted with the following functional groups: C1-C6 alkyl, C1-C6 alkoxy, halogen, C3-C8 cycloalkyl, phenyl, benzyl, C1-C4 alkylphenyl, C1-C4 alkoxyphenyl, halophenyl, C1-C4 alkylbenzyl, C1-C4 alkoxybenzyl, halobenzyl, or a five-membered, six-membered, or seven-membered heterocyclic structure containing two oxygen elements; R 3 is: hydrogen, unsubstituted or C1-C6 alkyl-substituted linear or branched C 1- C 16 Alkyl, C2-C 18 Alkoxyalkyl, C3-C8 cycloalkyl, phenyl or benzyl; X is S; and n is an integer from 2 to a value sufficient to give a molecular weight of about 500,000.
69. The method for forming an electrolytic capacitor of claim 68, wherein R in Formula B 1 and R 2 Together for -O-(CHR 4 )mO, where: m is an integer from 1 to 5; R 4 are independently selected from: hydrogen; linear or branched C1 to C 18 Alkyl, C5 to C 12 Cycloalkyl, C6 to C 14 Aryl, C7 to C 18 Aralkyl or C1 to C4 hydroxyalkyl, which is unsubstituted or substituted with a functional group selected from the group consisting of carboxylic acid, hydroxyl, amine, olefin, acrylate, thiol, alkyne, azide, sulfate, sulfonate, sulfonic acid, imide, amide, epoxy, anhydride, silane and phosphate; hydroxyl; -(CHR 5 ) a -R 16 ;-O(CHR 5 ) a R 16 ; -CH2O(CHR 5 ) a R 16 ; or -CH2O(CH2CHR 5 O) a R 16 ;or R 4 is a functional group selected from the group consisting of hydroxyl, carboxyl, amine, epoxy, amide, imide, anhydride, hydroxymethyl, olefin, thiol, alkyne, azide, sulfonic acid, benzenesulfonic acid sulfate, SO3M, anhydride, silane, acrylate and phosphate; R 5 is H or an alkyl chain containing 1 to 5 carbons, which is unsubstituted or substituted with a functional group selected from carboxylic acid, hydroxyl, amine, olefin, thiol, alkyne, azide, epoxy, acrylate and anhydride; R 16 is H, -SO3M or an alkyl chain containing 1 to 5 carbons, which is unsubstituted or substituted with a functional group selected from carboxylic acid, hydroxyl, amine, olefin, thiol, alkyne, azide, amide, imide, sulfate, -SO3M, amide, epoxy, anhydride, silane, acrylate and phosphate; a is an integer from 0 to 10; and M is H or a cation selected from ammonia, sodium or potassium.
70. The method for forming an electrolytic capacitor of claim 68 wherein the polymer is 3,4-polyethylenedioxythiophene.
71. The method of forming an electrolytic capacitor of claim 68, wherein the polymer is selected from the group consisting of poly(3,4-ethylenedioxythiophene), poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)-1-butane-sulfonic acid, salt), poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)-1-propane-sulfonic acid, salt), poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)-1-methyl-1-propane-sulfonic acid, salt), poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy alcohol, poly(N-methylpyrrole), poly(3-methylpyrrole), poly(3-octylpyrrole), poly(3-decylpyrrole), poly(3-dodecylpyrrole), poly(3,4-dimethylpyrrole), poly(3,4-dibutylpyrrole), poly(3-carboxypyrrole), poly(3-methyl-4-carboxypyrrole), poly(3-methyl-4-carboxyethylpyrrole), poly(3-methyl-4-carboxybutylpyrrole), poly(3-hydroxypyrrole), poly(3-methoxypyrrole), polythiophene thiophene, poly(3-methylthiophene), poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxy ... thiophene), poly(3-dodecyloxythiophene), poly(3-octadecyloxythiophene), poly(3,4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butenedioxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), poly(3-methyl-4-carboxybutylthiophene), polyaniline, poly(2-methylaniline), poly(3-isobutylaniline), poly(2-aniline sulfonate) and poly(3-aniline sulfonate).
72. The method of forming an electrolytic capacitor of claim 68 wherein the polymer is selected from the group consisting of poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)-1-butanesulfonic acid, salt), poly(4-(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy)-1-methyl-1-propanesulfonic acid, salt), poly(N-methylpyrrole), poly(3-methylthiophene), poly(3-methoxythiophene), and poly(3,4-ethylenedioxythiophene).
Citation Information
Patent Citations
Process to improve coverage and electrical performance of solid electrolytic capacitors
US10109428B2
Polyanion copolymers for use with conducting polymers in solid electrolytic capacitors
US10340091B2
Conductive polymer dispersion with enhanced coverage
US10643796B2
Conductive polymer dispersion for improved reliability
US10650980B2
Process for forming a solid electrolytic capacitor
US10658121B2